Pengaruh Pengetahuan Tentang Galeri Investasi Syariah Terhadap Minat Mahasiswa Membuka Rekening Saham - Ahmad Zaini; Mukhlis Kaspul Anwar; Lola Malihah (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to determine the effect of knowledge about sharia investment galleries on student interest in opening stock accounts at the Sharia Investment Gallery of Institut Agama Islam Darussalam Martapura. This study Â uses quantitative research, the data obtained will be in the form of numbers andÂ be analyzed further using statistical analysis software. This study consists of two variables, namely student knowledge as the variable X and interest in opening an account as the variable Y. The data analysis technique used is simple and partial regression. The population in this study were students of the Faculty of Islamic Economics and Business, Institut Agama Islam Darussalam Martapura, using Slovin formula as sampling method. The number of samples obtained was 70, from the existing population of 223 students.Â The results showed that the knowledge variable had a positive and significant effect on the interest in opening an account. It is proven that from the results of the validity test on the knowledge and interest variables, it can be seen that the Pearson correlation value is > 0.235 and the Sig (2-tailed) value is < 0.05 (valid). In the reliability test, the Cronbach's Alpha value obtained from knowledge is 0.841 and the Cronbach's Alpha value is from interest 0.883 > 0.600, thus the X and Y variables can be said to be reliable or reliable.